Is Cyber Diplomacy Essential in the Present Perspective? - Shrestha, Madhavji (Journal of Foreign Affairs, 2023)
It is now obvious that cyber space is the last frontier of man’s research and relevant activities to empirically learn about its multi-dimensionality and its immensely huge prospect. The quest is certainly increasing each passing day. The meteoric development of information technology together with scientific development has tremendously helped to push ahead its advance in recent decades, and in particular, the advanced and developed countries of the world have steadily made their efforts in carrying out their preferred activities and to know about what lies in the future for humanity on the earth. They have, at their disposal, human resources, capital resources, and material resources with compatible managerial skills to move on toward what they have projected as their goals for their countries and citizens. As cyber space has drawn the attention of the people around the world, it has emerged as the common concern of humanity. In reality, it has touched upon human activities mainly related with scientific, technological and socio-economic domains. Naturally, diplomatic activities that regulate and act on state-to-state and government-to government relations could not remain exempt, and nor touched upon as human security, and social and economic security are closely linked together. The human security and human welfare are closely related with activities in the cyber space. As a consequence, diplomacy connected with the cyber space has now come up as an unavoidable activity, not alone in technologically advanced countries but even in all the countries of the world as humans have to live and work in their respective territorial domains. Cyber space is the common concern of all the mankind. Hence, a pressing need for cyber diplomacy is essentially felt to have its own traction that can ensure amicable and friendly relations among all independent and sovereign countries of the world. A globally acceptable convention and practice of cyber diplomacy is also required to regulate its handlings and relevant activities. This piece tries to show how cyber diplomacy has come to occupy an iconic status in diplomatic ventures worldwide with its importance growing rapidly as pushed by information technology.